Hypertension control after an initial cardiac event among Medicare patients with diabetes mellitus: A multidisciplinary group practice observational study. Issue 5 (23rd April 2018) - Chaddha, Ashish; Smith, Maureen A.; Palta, Mari; Johnson, Heather M.
Abstract : Patients with diabetes mellitus and cardiovascular disease have a high risk of mortality and/or recurrent cardiovascular events. Hypertension control is critical for secondary prevention of cardiovascular events. The objective was to determine rates and predictors of achieving hypertension control among Medicare patients with diabetes and uncontrolled hypertension after hospital discharge for an initial cardiac event. A retrospective analysis of linked electronic health record and Medicare data was performed. The primary outcome was hypertension control within 1 year after hospital discharge for an initial cardiac event. Cox proportional hazard models assessed sociodemographics, medications, utilization, and comorbidities as predictors of control. Medicare patients with diabetes were more likely to achieve hypertension control when prescribed beta‐blockers at discharge or with a history of more specialty visits. Adults ≥ 80 were more likely to achieve control with diuretics. These findings demonstrate the importance of implementing guideline‐directed multidisciplinary care in this complex and high‐risk population.